Synthesis of Ca14Zn6Al10O35:Mn4+, Nd3+ phosphor using starch as an impregnation medium - Soo-Jong Kim (Journal of ceramic processing research, 2023)
Ca14Zn6Al10O35:Mn4+, Nd3+ phosphors were prepared by a liquid phase impregnation method. The results of XRD, SEM, andEDS analysis confirmed that pure CZA:Mn4+ and CZA:Mn4+, Nd3+ phosphors with single phases were synthesized. The Mn4+doped phosphors exhibited strong red emission in the range of 600 to 850 nm when excited at a wavelength of 356 nm. Theluminescence properties were investigated according to changes in the concentrations of Mn4+ and Nd3+ ions. The particle sizesof the phosphor when fired at 1200 °C for 3 hours were 100 to 500 nm. KCI Citation Count: 1